Sustainable healthy eating behaviour of young adults: towards a novel methodological approach - Zuzanna Pieniak; Sylwia Żakowska-Biemans; Eliza Kostyra; Monique Raats (BMC, 2016)
Abstract Background Food, nutrition and health policy makers are poised with two pertinent issues more than any other: obesity and climate change. Consumer research has focused primarily on specific areas of sustainable food, such as organic food, local or traditional food, meat substitution and/or reduction. More holistic view of sustainable healthy eating behaviour has received less attention, albeit that more research is emerging in this area. Methods/design This study protocol that aims to investigate young consumers' attitudes and behaviour towards sustainable and healthy eating by applying a multidisciplinary approach, taking into account economical, marketing, public health and environmental related issues. In order to achieve this goal, consumers' reactions on interactive tailored informational messages about sustainable from social, environmental and economical point of view, as well as healthy eating behaviour in a group of young adults will be investigated using randomized controlled trial. To undertake the objective, the empirical research is divided into three studies: 1) Qualitative longitudinal research to explore openness to adopting sustainable healthy eating behaviour; 2) Qualitative research with the objective to develop a sustainable healthy eating behaviour index; and 3) Randomised controlled trial to describe consumers' reactions on interactive tailored messages about sustainable healthy eating in young consumers. Discussion To our knowledge, this is the first randomised controlled trial to test the young adults reactions to interactive tailor made messages on sustainable healthy eating using mobile smartphone app. Mobile applications designed to deliver intervention offer new possibilities to influence young adults behaviour in relation to diet and sustainability. Therefore, the study will provide valuable insights into drivers of change towards more environmentally sustainable and healthy eating behaviours. Trial registration NCT02776410 registered May 16, 2016.